Multiple asteroid systems from the UkrVO digitized photographic plates - Kazantseva, L.; Shatokhina, S.
Several catalogs of various celestial objects were compiled based on the processing of Ukrainian VO archives and observatories in Kitab (Uzbekistan) and Baldone (Latvia). We analyzed the catalogs of asteroid positions and B-magnitudes obtained from the processing of digitized photographic plates and selected from them asteroids, which are known as multiple. Positional observations cover the period 1973-1993 and may be useful for a more detailed study of the dynamics of these systems. The obtained photometric characteristics of asteroids will be useful for studying changes in brightness.
Keywords: Astronomy